Cristalização e morfologia dos sistemas PBT/PCL e PC/PCL - Almeida, Debora Evelyn de Oliveira (2019)
Polycarbonate (PC) is an amorphous thermoplastic very known for its excellent properties, such as high transparency and good dimensional stability. However, it has some drawbacks which limit its use in several applications, such as notch sensitivity; these can be solved by mixing PC with polymers which have a higher plasticizer action. Polybuthylene Terephthalate (PBT), is a semi-crystalline polymer that has good thermal stability, excellent processing properties and fast crystallization rate. Also, some of its undesired properties can be improved by mixing with other polymers. Therefore, in this work, blends of these polymers with poly (ε-caprolactone) (PCL), which has macromolecular regularity becoming highly crystallizable and thus improving its mechanical properties. Based on above mentioned, the objective of this work was producing PBT/PCL and PC/PCL blends, evaluating crystallization, observing the morphology and studying their toughening. The blends were prepared in an internal Haake Rheomix 600 laboratory mixer. The morphologies and fracture behavior were investigated by scanning electron microscopy (SEM), through this technique it was also possible to analyze the effect of PCL toughening when added to PC. For PBT/PCL system, the melting and crystallization phase transitions were studied by differential scanning calorimetry (DSC), and its thermal stability was evaluated by Thermogravimetry (TG). No degradation signs were verified during blends processing, and these presented positive compatibility. It has been found that PC toughening can be achieved upon PCL addition, while the crystallinity and properties of PBT/PCL blends can be controlled by the heating/cooling rates as well as through PCL addition.